Hibah Naskah DREAMSEA dan Strategi Pelestarian Ingatan Kolektif Nusantara - Lilis Shofiyanti; Hadi Rahman (Manuskripta, 2025)
The preservation of Nusantara manuscripts is not merely a philological task but a cultural practice demanding activism, advocacy, and the active involvement of manuscript owners as guardians of collective memory. Ancient manuscripts serve as both historical artifacts and living sources of knowledge continuously negotiated within their owning communities. In 2024, DREAMSEA (Digital Repository of Endangered and Affected Manuscripts in Southeast Asia) donated eight years of digitization results to the National Library of Indonesia, marking the largest grant in the institution’s history. This momentum represents three key dimensions: first, knowledge activism rooted in ethical relationships with manuscript owners; second, institutional advocacy that strengthens the state’s role without diminishing the cultural authority of local communities; and third, transnational collaboration transformed into national legitimacy. The DREAMSEA grant demonstrates that ideal manuscript preservation is built upon an equal partnership between owners, local communities, and state institutions. Integrating community roles with state policy support is essensial to ensure manuscripts remain living, accessible knowledge sources for the future of Indonesian philology. === Pelestarian naskah Nusantara tidak semata kerja filologis, melainkan praktik kultural yang menuntut aktivisme, advokasi, dan keterlibatan pemilik manuskrip sebagai penjaga ingatan kolektif. Naskah kuno berfungsi sebagai artefak historis dan sumber pengetahuan hidup yang terus dinegosiasikan dalam komunitas pemiliknya. Pada 2024, DREAMSEA (Digital Repository of Endangered and Affected Manucripts in Southeast Asia) menghibahkan hasil digitalisasi naskah selama delapan tahun kepada Perpustakaan Nasional RI, menjadi hibah terbesar dalam sejarah lembaga tersebut. Momentum ini merepresentasikan tiga dpertama, aktivisme pengetahuan yang berangkat dari relasi etis dengan pemilik manuskrip; kedua, advokasi institusional yang memperkuat peran negara tanpa meniadakan otoritas kultural komunitas; dan ketiga, kolaborasi transnasional yang bertransformasi menjadi legitimasi nasional. Hibah DREAMSEA memperlihatkan bahwa pelestarian naskah idealnya dibangun atas kemitraan setara antara pemilik manuskrip, komunitas lokal, dan institusi negara. Integrasi peran masyarakat dan dukungan kebijakan negara sangat penting untuk memastikan naskah tetap hidup sebagai sumber pengetahuan yang bisa diakses bagi masa depan filologi Indonesia.